Study of Rural Industries Projects Design Schedules Etc. and Instructions Programme Evaluation Organisation Planning Commission New Delhi-1973 - Planning Commission (Planning Commission, 1973)
The document focuses on the methodologies, objectives, sampling designs, and guidelines associated with the study of Rural Industries Projects (RIP), aimed at enhancing rural economies. It highlights the collaborative efforts of officers from various levels, field officers, and representatives from industrial development ministries. By understanding these components, stakeholders can assess and potentially enhance the effectiveness of rural industrial programs, making substantial improvements in local economies. The comprehensive nature of this study indicates a serious commitment to fostering sustainable rural development.
Programme Evaluation Organisation Planning Commission
Programme Evaluation Organisation Planning Commission
Keywords: Rural Industries Projects; Training Opportunities; Tools and Resources; Income and Employment Status; Feedback on Training; Workers in rural areas; Identifying and Enhancing skills